Distance Learning in Vocational High Schools during the COVID-19 Pandemic in West Java Province, Indonesia - Mulyanti, Budi; Purnama, Wawan; Pawinanto, Roer Eka (Universitas Pendidikan Indonesia, 2020)
This study aims to investigate (1) the availability of learning facilities for distance learning (or online learning), (2) the ability of students and teachers to utilize the learning facilities, and (3) how distance learning activities take place at public or private vocational high schools, specifically whether it is perceived to be more interesting than ordinary learning. This study used a survey method to obtain data and a quantitative descriptive method to analyze the data. The type of data in this study was primary based on the responses of respondents or individuals from groups representing the population of public and private vocational high schools, especially in the Electrical Engineering Clusters in the entire areas of West Java. The results revealed that online learning has been carried out in many public and private vocational high schools in West Java. This study indicates that the availability of online learning facilities, the utilization of facilities, and the online learning process in public vocational high schools were better than those in private vocational high schools. In general, students of both public and private vocational high schools stated that online learning is not more interesting than ordinary learning, although most of them can understand the lessons taught and they were given an opportunity by their teachers to actively participate during the learning process.